Material cosmopolitanism: the entrepot of Harlaa as an Islamic gateway to eastern Ethiopia. (April 2021) - Insoll, Timothy; Khalaf, Nadia; MacLean, Rachel; Parsons-Morgan, Hannah; Tait, Nicholas; Gaastra, Jane; Beldados, Alemseged; Pryor, Alexander J.E.; Evis, Laura; Dussubieux, Laure
Abstract: Abstract : The investigation of Islamic archaeology in Ethiopia has until recently been neglected. Excavations at Harlaa, a large urban centre in eastern Ethiopia, are now beginning to redress this lack of research attention. By establishing occupation and material sequences, and by assessing the chronology and material markers of Islamisation, recent work provides important new insight on the presence and role of Muslims and Islamic practice at Harlaa, and in the Horn of Africa more generally. The results challenge previous assumptions of cultural homogeneity, instead indicating the development of cosmopolitanism. They also suggest a possible historical identity for Harlaa: as Hubät/Hobat, the capital of the Hārlā sultanate.